2000
DOI: 10.1177/00220345000790060501
|View full text |Cite
|
Sign up to set email alerts
|

Co-ordinated Mandibular and Head-Neck Movements during Rhythmic Jaw Activities in Man

Abstract: Recent observations in man of concomitant mandibular and head movements during single maximal jaw-opening/-closing tasks suggest a close functional relationship between the mandibular and the head-neck motor systems. This study was aimed at further testing of the hypothesis of a functional integration between the human jaw and neck regions. Spatiotemporal characteristics of mandibular and associated head movements were evaluated for 3 different modes of rhythmic jaw activities: self-paced continuous maximal ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
1
24

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 32 publications
12
128
1
24
Order By: Relevance
“…The start of head extension generally precedes the beginning of jaw opening, which indicates the anticipatory adjustment of the head position preparatory to jaw movement 5 . The muscles of the jaw and neck have associated movements and changes in one of the structures can disrupt the other.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The start of head extension generally precedes the beginning of jaw opening, which indicates the anticipatory adjustment of the head position preparatory to jaw movement 5 . The muscles of the jaw and neck have associated movements and changes in one of the structures can disrupt the other.…”
Section: Resultsmentioning
confidence: 97%
“…Likewise, the correct head extension obtains biomechanical advantages which promote coordination between the head and jaw and enhances force production during bite 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, in symptomatic patients with whiplash, head extension was absent in opening and closing of the participants' jaw. 17 Our results support these findings of differentiation of symptomatic and asymptomatic populations and suggests that no significant change in jaw opening reflects the absence of alterations often seen in symptomatic populations.…”
Section: Discussionmentioning
confidence: 99%
“…7 During normal mouth opening, extension occurs at the cervical-cranial junction; and restriction in the upper cervical spine may decrease a patient's mouth-opening capacity. 10 De Laat et al 11 found that segmental limitations in the upper cervical spine (C0-C3) were significantly more present in patients with TMD than controls.…”
Section: Introductionmentioning
confidence: 99%